Morvern callar [videorecording (Blu-Ray)] - Ramsay, Lynne, 1969-; Dognini, Liana; Morton, Samantha; McDermott, Kathleen, 1978- (Fun City Editions, 2022)
Morvern Callar is greeted with a startling surprise, her boyfriend has committed suicide. He has left her a cryptic message on his computer and a manuscript for a novel. She changes the author's name to her own and begins a re-birth of self discovery.